Detection of Translocation of Cochlear Implant Electrode Arrays by Intracochlear Impedance Measurements. Issue 5 (8th September 2021) - Dong, Yu; Briaire, Jeroen J.; Siebrecht, Michael; Stronks, H. Christiaan; Frijns, Johan H. M.
Abstract : Objectives: Misplacement of the electrode array is associated with impaired speech perception in patients with cochlear implants (CIs). Translocation of the electrode array is the most common misplacement. When a CI is translocated, it crosses the basilar membrane from the scala tympani into the scala vestibuli. The position of the implant can be determined on a postoperative CT scan. However, such a scan is not obtained routinely after CI insertion in many hospitals, due to radiation exposure and processing time. Previous studies have shown that impedance measures might provide information on the placement of the electrode arrays. The electrode impedance was measured by dividing the plateau voltage at the end of the first phase of the pulse by the injected current. The access resistance was calculated using the so-called access voltage at the first sampled time point after the start of the pulse divided by the injected current. In our study, we obtained the electrode impedance and the access resistance to detect electrode translocations using electrical field imaging. We have investigated how reliably these two measurements can detect electrode translocation, and which method performed best. Design: We calculated the electrode impedances and access resistances using electrical field imaging recordings from 100 HiFocus Mid-Scala CI (Advanced Bionics, Sylmar, CA) recipients. We estimated the normal values of these two measurements as the baselines of the implant placed in the cochlea without translocation. Next, we calculated the maximal electrode impedance deviation and the maximal access-resistance deviation from the respective baselines as predictors of translocation. We classified these two predictors as translocations or nontranslocations based on the bootstrap sampling method and receiver operating characteristics curves analysis. The accuracy could be calculated by comparing those predictive results to a gold standard, namely the clinical CT scans. To determine which measurement more accurately detected translocation, the difference between the accuracies of the two measurements was calculated. Results: Using the bootstrap sampling method and receiver operating characteristics–based optimized threshold criteria, the 95% confidence intervals of the accuracies of translocation detections ranged from 77.8% to 82.1% and from 89.5% to 91.2% for the electrode impedance and access resistance, respectively. The accuracies of the maximal access-resistance deviations were significantly larger than that of the maximal electrode impedance deviations. The location of the translocation as predicted by the access resistance was significantly correlated with the result derived from the CT scans. In contrast, no significant correlation was observed for the electrode impedance. Conclusions: Both the electrode impedance and access resistance proved reliable metrics to detect translocations for HiFocus Mid-Scala electrode arrays. The access resistance had, however, significantly better accuracy and it also reliably detected the electrode-location of translocations. The electrode impedance did not correlate significantly with the location of translocation. Measuring the access resistance is, therefore, the recommended method to detect electrode-array translocations. These measures can provide prompt feedback for surgeons after insertion, improving their surgical skills, and ultimately reducing the number of translocations. In the future, such measurements may allow near-real-time monitoring of the electrode array during insertion, helping to avoid translocations.